Spatiotemporal coordination of FGF and Shh signaling underlies the specification of myoblasts in the zebrafish embryo - Yin, Jianmin (2020)
Somitic cells give rise to a variety of cell types in response to Hh, BMP, and FGF signaling. Cell position within the developing zebrafish somite is highly dynamic: how, when, and where these signals specify cell fate is largely unknown. Combining four-dimensional imaging with pathway perturbations, we characterize the spatiotemporal specification and localization of somitic cells. Muscle formation is guided by highly orchestrated waves of cell specification. We find that FGF directly and indirectly controls the differentiation of fast and slow-twitch muscle lineages, respectively. FGF signaling imposes tight temporal control on Shh induction of slow muscles by regulating the time at which fast-twitch progenitors displace slow-twitch progenitors from contacting the Shh-secreting notochord. Further, we find a reciprocal regulation of fast and slow muscle differentiation, morphogenesis, and migration. In conclusion, robust cell fate determination in the developing somite requires precise spatiotemporal coordination between distinct cell lineages and signaling pathways.